TOWARDS SUSTAINABLE PROSPERITY: EXPLORING ALTERNATIVE ENERGY SOLUTIONS FOR ECONOMIC GROWTH IN UZBEKISTAN - Djemilov Ridvan Narimanovich; Kurpayanidi K.I. (Web of Journals Publishing, 2024)
This article critically examines the potential of alternative energy sources to drive economic development while fostering sustainability in Uzbekistan's energy sector. Through a meticulous analysis of the country's current energy landscape, renewable energy potential, and policy frameworks, the study elucidates the opportunities and challenges associated with transitioning to sustainable energy practices. Drawing on international experiences and best practices, the article offers strategic insights and recommendations for policymakers, stakeholders, and investors to promote the adoption of alternative energy solutions and create an enabling environment for sustainable economic growth. By highlighting the economic, environmental, and social benefits of alternative energy development, this research underscores the imperative for Uzbekistan to embrace renewable energy as a pathway towards long-term prosperity and environmental stewardship.
Keywords: Alternative energy, Uzbekistan, Economic growth, Sustainability, Renewable energy, Energy sector, Policy frameworks, Transition, Environmental stewardship, Sustainable development.